Meta-analysis of a Holocene 14C database for the detection of paleohydrological crisis in the Venetian–Friulian Plain (NE Italy) - ROSSATO, SANDRO; FONTANA, ALESSANDRO; MOZZI, PAOLO (CATENA, 2015)
The Venetian–Friulian Plain is the northernmost alluvial environment facing the Adriatic Sea and it represents the transition from theMediterranean domain to the Alps and the temperate regions of central and eastern Europe. The investigated area consists of the alluvial systems of Brenta, Piave and Tagliamento rivers, forming distinct alluvial megafans fed bymountain basins of 1567, 3899 and 2580 km2, respectively. The database of radiocarbon dates related to theHolocene alluvial evolution of the Venetian–Friulian Plain consists of 136 samples, 65 of them classified as change-after dates. We analyzed statistically the database with the aim of detecting periods of enhanced flooding activity. The individual calibration probability intervals of each radiocarbon age were summed, producing a cumulative probability density function (CPDF) plot for each alluvial systemand for thewhole database. Each change-after CPDF plot has been subtracted to its correspondent CPDF plot of the entire sub-dataset, obtaining a relative cumulative probability function (RCPF) curve. The analysis of these curves evidences that statistically significant information are available between about 8.5 and 0.8 ka cal BP. In particular, nine periods of enhanced flooding activity have been identified: 8.4–8.3, 7.5– 7.2, 6.9–6.2, 5.5–5.3, 4.7–4.5, 2.3–2.1, 1.9–1.7, 1.6–1.4 and 1.3–0.8 ka cal BP. In the interval 8.5–0.8 ka cal BP, some sub-periods are not statistically significant because of the relatively fewchange-after dates available. Notably, between 4.5 and 2.3 ka cal BP no interval has been recognized, even if some important flooding deposits are documented in the stratigraphic and geomorphological record. Meta-analyses revealed quite a good correlation of several flooding periods occurred in the study area with the flooding record of the Lake Iseo (northern Italy), as well as with positive peaks in the Ice Rafted Debris (IRD) curve for the North Atlantic, namely Bond events 1, 3, 4 and 5. Comparison with other flood sequences obtained in ...